Engines of Sectoral Labor Productivity Growth - Zsofia Barany; Christian Siegel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We study the origins of labor productivity growth and its differences across sectors. In our model, sectors employ workers of different occupations and various forms of capital, none of which are perfect substitutes, and technology evolves at the sector-factor cell level. Using the model we infer technologies from US data over 1960-2017. We find sector-specific routine labor augmenting technological change to be crucial. It is the most important driver of sectoral differences, and has a large and increasing contribution to aggregate labor productivity growth. Neither capital accumulation nor the occupational employment structure within sectors explains much of the sectoral differences.
Keywords: O41; O33; J24; 330; biased technological change; structural transformation; labor productivity